2014
DOI: 10.1371/journal.pone.0100557
|View full text |Cite
|
Sign up to set email alerts
|

LIM and SH3 Domain Protein 1 (LASP-1) Overexpression Was Associated with Aggressive Phenotype and Poor Prognosis in Clear Cell Renal Cell Cancer

Abstract: BackgroundLIM and SH3 protein 1 (LASP-1) is a specific focal adhesion protein that is known to be involved in numerous biological and pathological processes. LASP-1 overexpression has been described in several types of cancers, but its expression and role in clear cell renal cell cancer (ccRCC) remains unknown.MethodsUsing immunohistochemistry, we analyzed LASP-1 protein expression in 216 clinicopathologically characterized ccRCC cases. We also examined LASP-1 expression in 20 paired ccRCC tissues and in 2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…A-498, the 786-0 cells exhibit higher expression of LIM and SH3 protein 1 (LASP-1), which correlated with aggressive phenotype and poor prognosis in RCC (20). Thus, the more aggressive cell line 786-0 was selected to investigate whether honokiol inhibits cell migration under the incubation time (3 h) and concentrations (0-40 µM) that do not affect viability of 786-0 cells.…”
Section: Honokiol Inhibits Migration Of 786-0 Cells Comparing Withmentioning
confidence: 99%
See 1 more Smart Citation
“…A-498, the 786-0 cells exhibit higher expression of LIM and SH3 protein 1 (LASP-1), which correlated with aggressive phenotype and poor prognosis in RCC (20). Thus, the more aggressive cell line 786-0 was selected to investigate whether honokiol inhibits cell migration under the incubation time (3 h) and concentrations (0-40 µM) that do not affect viability of 786-0 cells.…”
Section: Honokiol Inhibits Migration Of 786-0 Cells Comparing Withmentioning
confidence: 99%
“…In this study, we first demonstrate that honokiol suppresses proliferation of human RCC A-498 and 786-0 cells without affecting cell viability. In addition, honokiol inhibits migration of highly metastatic RCC 786-0 (19,20) and stimulates RhoA activity. Furthermore, phosphorylated MLC and excessive formation of actin stress fibers were identified in 786-0 cells treated with honokiol.…”
Section: Introductionmentioning
confidence: 99%
“…LASP-1 is a speci c focal adhesion protein that has been demonstrated to play an important role in cancer development and progression [13,[29][30][31]. For instance, Frietsch et al analyzed the prognostic signi cance of LASP-1 in breast cancer patients and provided evidence that nuclear LASP-1-positivity may serve as a negative prognostic indicator for long-term survival of breast cancer patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al determined the expression of LASP-1 in primary HCC and the results showed that the high cytosolic LASP-1 expression was associated with poor overall survival in HCC patients [30]. Yang et al examined LASP-1 expression in ccRCC tissues and in two cell lines and the results indicated that LASP-1 might serve as a prognostic biomarker for ccRCC patients [31]. Based on the previous reports, we studied the clinical diagnostic value of LASP-1 in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…invasion, and metastasis process. [8][9][10][11][12][13][14][15] However, unlike Lasp1, little is known about the function of Lasp2 in human cancers.…”
mentioning
confidence: 99%